ini, dan, dari CITA KARA: JURNAL PENCIPTAAN DAN STUDI SENI MURNI: WARNA BIPOLAR SEBAGAI IDE UNTUK MEMBUAT KARYA SENI YANG BAIK - aristi, dewa ayu sakania pradnya; Sujana, I Wayan; Purnami , Ni Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
People with bipolar disorder often experience dramatic mood swings, characterized by manic, depressive and mixed symptoms. Drastic emotional changes include feelings of happiness, sadness, fear and other excessive emotions. By using the theory of color psychology, the author wants to visualize facial expressions that come from drastically changing emotional colors. These colors are combined in the opposite way like bipolar traits, resulting in new colors that are visualized in the form of facial expressions "Comfortable, Enthusiastic, Calm, Lack of Confidence, Graceful, Romantic and Patient".The method of creation is carried out through the stages of exploration or search for ideas, improvisation or experimentation, namely conducting various trials of techniques, compositions, sketch forms, blocking, combining materials, and trials of techniques such as paint melting techniques, marker and palette strokes, splashes, twig blows, and stamps; and formation, namely realizing it in the form of aesthetic works and in accordance with aesthetic works and in accordance with aesthetic and artistic experiences.